Understanding the behavioral intention of rural women to engage in green poultry farming: A psychological analysis - Pouria Ataei; Hamed Ghadermarzi; Hamid Karimi; Meysam Menatizadeh; Nasim Izadi (Results in Engineering)
Promoting sustainable agricultural practices requires an understanding of the psychological factors that influence behavioral intentions, particularly among rural women who play a pivotal role in local food systems. This study explores rural women's intention to adopt green poultry farming as a sustainable and healthy production approach using the Health Belief Model (HBM). The research was conducted among 875 rural women participating in a joint project of the Japan International Cooperation Agency (JICA) in Iran. A sample of 420 women was selected using a multi-stage clustering technique, and data were gathered through structured interviews. Statistical analysis was conducted with SPSS and PLS software to evaluate the relationships between HBM constructs and behavioral intention. The results indicated that perceived benefits, perceived susceptibility, cues to action, and conformity significantly influenced rural women's intention to produce green poultry, collectively explaining 51 % of the variance. The study underscores the importance of perceived health and environmental benefits as critical motivators, suggesting that targeted awareness campaigns and social support systems could enhance women's engagement in green poultry farming. By leveraging the psychological dimensions of HBM and fostering community-based approaches, policymakers can design interventions that not only promote sustainable practices but also empower rural women as agents of change in advancing food security and environmental sustainability. This research contributes to the growing body of knowledge on sustainable agriculture and highlights the need for gender-sensitive strategies in rural development.